Introduction to Contracts, Sales and Product Liability - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K. (Open textbook library., 2012)
This textbook provides context and essential concepts across the entire range of legal issues with whichmanagers and business executives must grapple. The text provides the vocabulary and legal acumennecessary for businesspeople to talk in an educated way to their customers, employees, suppliers,government officials—and to their own lawyers. Traditional publishers often create confusion among customers in the text selection process by offering ahuge array of publications. Once a text is selected, customers might still have to customize the text to meettheir needs. For example, publishers usually offer books that include either case summaries or excerptedcases, but some instructors prefer to combine case summaries with a few excerpted cases so that studentscan experience reading original material. Likewise, the manner in which most conventional textsincorporate video is cumbersome because the videos are contained in a separate library, which makesaccess more complicating for instructors and students.